2012
DOI: 10.1007/s00396-012-2598-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface free energy of polyurethane coatings with improved hydrophobicity

Abstract: The polarity of polyurethane coats was studied on the basis of the goniometric method for determination of wetting angle values, on the basis of calculated surface free energy (SFE) values by the van Oss–Good and Owens–Wendt methods, and on the basis of polarity measurements with the use of the 1H NMR spectra. Test polyurethanes were synthesised in the reaction of methylene diphenyl 4,4′-diisocyanate (MDI) or 3-izocyanatomethyl –3,5,5- trimethylcyclohexyl isocyanate (IPDI) and polyoxyethylene glycols or polyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…In this case, the observed signal, situated at 3330 cm −1 suggests that most of the N─H groups are involved in hydrogen bonds. The peak around 1735 cm −1 corresponds to the CO vibration of PCL and urethane group, whereas a signal situated at 1640 cm −1 is attributed to hydrogen bonded CO of urea groups . The peak situated at 1550 cm −1 in Amide II region is assigned to the C─N stretching vibration and N─H bending of urethane groups.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In this case, the observed signal, situated at 3330 cm −1 suggests that most of the N─H groups are involved in hydrogen bonds. The peak around 1735 cm −1 corresponds to the CO vibration of PCL and urethane group, whereas a signal situated at 1640 cm −1 is attributed to hydrogen bonded CO of urea groups . The peak situated at 1550 cm −1 in Amide II region is assigned to the C─N stretching vibration and N─H bending of urethane groups.…”
Section: Resultssupporting
confidence: 90%
“…The peak around 1735 cm −1 corresponds to the C O vibration of PCL and urethane group, 45 whereas a signal situated at 1640 cm −1 is attributed to hydrogen bonded C O of urea groups. 46 The peak situated at 1550 cm −1 in Amide II region is assigned to the C─N stretching vibration and N─H bending of urethane groups. The band located around 1460 cm −1 corresponds to ─CH 2 ─ stretching band and the signal situated at 1024 cm −1 is assigned to C─O stretching vibration.…”
Section: Films Characterizationmentioning
confidence: 99%
“…For the samples with relatively low inulin content (PU-INU33 and PU-INU50) it is observed that both have a similar mechanic and thermic properties compared to a hydrophilic polyurethane synthesized with PCL-diol or even as a polyurethane-based on diisocyanate with ether group such as poly(oxyethylene) glycol [49], this due to the presence of inulin chains. These polyurethane materials can uptake water by hydrogen bonding since the molecule has available link sites in contrast with the sample with the highest inulin content (PU-INU66) which has less amount of available link sites due to the presence of more free inulin that could also hydrolyze and make the structure unstable [60][61][62][63][64]. PU-INU50 presented a balance on mechanical and thermal properties which is reflected in a balanced structure with inulin in urethane linkage and non-bonded which gives the highest swelling capacity of all the samples.…”
Section: Discussionmentioning
confidence: 99%
“…As the IPDI/(PCL + DMPA) molar ratio increases the band associated to N H stretching vibration of urethane group at 3290 cm −1 [1,11] increases due to the higher quantity of urethane linkages. Moreover, a new band related to C N stretching and N H bending of urethane functional group, in amide II region, can be observed at 1527 cm −1 [22], which increases in intensity as IPDI/(PCL + DMPA) molar ratio increases. In order to study the influence of reagents molar ratio in the formation of urethane band and also hydrogen bonding, an amplification of the carbonyl stretching region is included in Fig.…”
Section: Properties Of Polyurethane Filmsmentioning
confidence: 93%